Low-flow behavior of alpine catchments with varying quaternary cover under current and future climatic conditions - Arnoux, Marie; Brunner, Philip; Schlaefli, Bettina; Mott, Rebecca; Cochand, Fabien; Hunkeler, Daniel (My University, 2020)
Alpine environments are particularly vulnerable to climatic warming, and long term observations suggest a shift of snow-influenced river discharge towards earlier periods of the year. For water resources management, the seasonal patterns of discharge in alpine areas are particularly relevant, as the shift to lower flows in summer and autumn combined with increased water demand could lead to water shortage in downstream catchments. The storage of groundwater in alpine catchments could significantly modulate how changing climatic conditions influence the annual streamflow regime. However, groundwater storage and its buffering capacity in alpine areas remain poorly understood. Moreover, studies on how climate change will impact water resources in alpine areas rarely consider the influence of geology. In this paper, catchment geology is used as a basis for the classification of future summer low flows behavior of several alpine catchments in Switzerland. Based on the analysis of the relationship between low-flow indicators and geology, the role of unconsolidated quaternary deposits is explored. We show that quaternary deposits play a critical role in the seasonal storage of groundwater, which can contribute to rivers during lowflow periods. Three climate change simulations based on extreme RCP 8.5 scenarios are fed into a conceptual hydrological model to illustrate the buffering role of groundwater. Past and future low flows normalized by mean past and future streamflows appear correlated with the percentage of unconsolidated quaternary deposits. These results highlight that catchments with high groundwater contribution to streamflow relative to precipitation will have a slower decrease in future summer discharge. Therefore, we propose two indicators that can be used to anticipate the response of future summers low flows in alpine areas to climate change: the current winter low flows and the percentage of unconsolidated quaternary deposits of the catchments.
Keywords: Hydrology; Alpine catchments; Groundwater storage; Snow; Climate change